Prevalence and determinants of caesarean section deliveries in the Kintampo Districts of Ghana - Daniel Gyaase; Yeetey Akpe Enuameh; Benjamin Noble Adjei; Stephaney Gyaase; Emmanuel Kweku Nakua; Moses Musah Kabanunye; Mohammed Muhib Alhassan; Mohammed Sheriff Yakubu; Richard Joshua Tetteh; Sam Newton; Kwaku Poku Asante (BMC, 2023)
Abstract Background Globally, the increasing rate of caesarean section (CS) delivery has become a major public health concern due to its cost, maternal, neonatal, and perinatal risks. In Ghana, the Family Health Division of the Ghana Health Service in 2016 opted to initiate a program to prevent the abuse of CS and identify the factors contributing to its increase in the country. This study aimed to determine the prevalence and factors influencing CS deliveries in the Kintampo Districts of Ghana. Methods The current study used secondary data from the Every Newborn-International Network for the Demographic Evaluation of Populations and their Health (EN-INDEPTH) project in Kintampo, Ghana. The outcome variable for this study is CS delivery. The predictor variables were socio-demographic and obstetric factors. Results The prevalence of CS delivery in the study area was 14.6%. Women with secondary education were 2.6 times more likely to give birth by CS than those with primary education. Unmarried women were about 2.5 times more likely to deliver by CS compared to those who were married. There was an increasing order of CS delivery among women in the wealthy quintiles from poorer to richest. The likelihood of women with gestational ages from 37 to 40 weeks to give birth by CS was about 58% less compared to those with less than 37 gestational weeks. Women who had 4-7 and 8 or more antenatal care (ANC) visits were 1.95 and 3.5 times more likely to deliver by CS compared to those who had less than 4 ANC visits. The odds of women who have had pregnancy loss before to deliver by CS was 68% higher compared to women who have not lost pregnancy before. Conclusions Caesarean section delivery prevalence in the study population was within the Ghana Health Service and World Health Organization ranges. In addition to known socio-demographic and obstetric factors, this study observed that a history of pregnancy loss increased the chances of a woman undergoing a CS. Policies should aim at addressing identified modifiable factors to stem the rise in CS deliveries.